Parasitoid guild and parasitism rate of the obliquebanded leafroller in IPM orchards and adjacent woodlands - Tremblay, Jacinthe; Cabrera, Paula; Cormier, Daniel; Brodeur, Jacques; Lucas, Éric (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2018)
The obliquebanded leafroller (OBLR), Choristoneura rosaceana (Harris) [Lepidoptera: Tortricidae], a primary pest in Quebec apple orchards, can be naturally parasitized. Knowing that habitats around crop’s peripheries are reservoirs for natural enemies of pests, the objective of the present investigation was to assess parasitism and parasitoid guild composition associated with the OBLR. The two-year study included orchards under integrated pest management, their edges, and adjacent woodlands. Parasitism was assessed using sentinel OBLR larvae and considered spring, early summer and late summer. Parasitism rates between regions with different vegetation composition were not significantly different. The first year, late summer larvae showed higher parasitism in orchards (27%), compared to edges (7%) and woodlands (11%). The following year, larvae exposed in early summer had higher parasitism rate in edges (28%) compared to orchards and woodlands (17% in both zones). Nineteen parasitoid species parasitized sentinel larvae. The tachinid Actia interrupta (Curran), the most abundant species, represented 28 and 62% of species the first and the second year respectively. Our research demonstrates that natural biological regulation of the OBLR is the result of a highly diversified parasitoid guild and this should be taken into account in any Integrated Pest Management program.